Summary proceedings of the sixty-first annual meeting of the Board of Governors : October 22, 2007 - International Monetary Fund.; International Monetary Fund. (Washington, DC. : International Monetary Fund, 2008)
The speeches made by officials attending the IMF-World Bank Annual Meetings are published in this volume, along with the press communiqués issued by the International Monetary and Financial Committee and the Development Committee at the conclusion of the meetings.
oif 08/09/2021
Ref.
Keywords: Debt Relief; Debt; Election; Oil prices; World Economy